(untitled) (PerCursos, 2022)
Rescuing the Marxist-Leninist tradition of investigation of national realities, Milton Santos raises the category of Sociospatial Formation, so dear to Lenin in his studies on Russia and the USA, to the level of an interpretive paradigm of Human Geography. Under the primacy of historical materialism, Sociospatial Formation sticks to the idea of totality and the dialectic between the universal and the particular. However, this category loses more strength every day within the scope of its own geography, especially by those who are influenced by a vulgar Marxism, without a vision of a historical process and “concrete analysis of the concrete situation”, as well as by those influenced by the postmodern wave that reached the human sciences with neoliberalism. Thus, the present article seeks to identify the contradictions between the category of Sociospatial Formation and (1) the circulationist perspective of world-system theory and (2) postmodern philosophy, both the antithesis of totality.